ChemInform Abstract: Scalable Total Synthesis of rac‐Jungermannenones B and C. Issue 27 (16th June 2016) - Liu, Weilong; Li, Houhua; Cai, Pei‐Jun; Wang, Zhen; Yu, Zhi‐Xiang; Lei, Xiaoguang
Abstract: Starting from geraniol, the ent‐kaurene‐type diterpenoids jungermannenone B (I) and C (II) are synthesized as racemates in 10 and 9 steps, respectively.